Evaluation of pressure losses due to solids-in-liquid pipe flow by CFD simulation - Al-Kayiem, H.H. (Asian Research Publishing Network, 2016)
One of the most important elements of liquids transportation process, mainly the crudes and oil products, is the pipelines flow assurance by maintaining lowest pressure losses. Existence of two phase flow in the pipe would generate different pressure drop than the designed drop under single phase flow assumption. This paper presents CFD simulation results of solid-in-liquid, i.e. slurry horizontal pipe flow using ANSYS-CFX software. The influencing of sand particles diameter and concentration on the pressure loss of pipelines at various flow rates of sand-in-Diesel 2D was studied. Three cases have been investigated; single liquid flow, homogeneous slurry sand-in-liquid flow, and two layers slurry flow, suspended layer in the upper and dead bed in the bottom. For validation, water flow was also simulated. Water and Diesel 2D were assumed Newtonian, incompressible and the region of simulation was fully developed. Mesh independency study was conducted so that the produced results would not be affected by the number of element. Fluid flow was simulated as single phase flow with velocities of 0.5, 1.0, 1.5 and 2.0 m/s. Then, particles were dispersed in the flow with volumetric concentrations of 10, 15 and 20. The investigated particles sizes were 0.25, 0.50 and 1.00 mm. The simulation procedure was validated through comparison of the pressure drop and friction factor results with the well-established methods in the literature. Analysis of the homogeneous solid-in-liquid flow results demonstrates an increase in the pressure drop. In the case of two-phase two-layer flow, the pressure drop increases dramatically due to the high shear between the upper and lower layers leading to very high resistance at the interface surface between the stationary bed and the upper homogenous layer. The simulation explores interesting phenomena of particle settling due to the high shear at the interface surface resulting in creation of moving bed between the layers. Further investigations will enhance the understanding of the multi layers slurry flow phenomena. Â© 2006-2016 Asian Research Publishing Network (ARPN). All rights reserved.